Literature Review of Salience and Financial Markets - Puuronen, Paavo (My University, 2025)
The purpose of this thesis is to examine the effect of salience on financial markets. More practically, this thesis examines how the salient information affects investment decisions on financial markets. Examples of salient information are extreme returns or news coverage. Furthermore, the purpose is to find out whether positive or negative information has a significantly larger impact on investors impacted by saliency. In the textbook, the markets are defined as efficient, and investors behave rationally and subsequently always maximize their utility in all circumstances. This thesis finds the answer to the research question supported by the hypotheses. It does so by covering the theoretical background of the topic and investigating relevant previous literature discussing the topic.

Tämän tutkielman tarkoituksena on tarkastella huomionarvoisuuden vaikutusta rahoitusmarkkinoihin. Käytännössä tutkielma tarkastelee, kuinka huomionarvoinen informaatio vaikuttaa sijoituspäätöksiin rahoitusmarkkinoilla. Esimerkkejä tällaisesta informaatiosta ovat poikkeukselliset tuotot tai saatu näkyvyys uutisissa. Tämän lisäksi tavoitteena on selvittää, onko positiivisella vai negatiivisella informaatiolla merkittävämpi vaikutus sijoittajiin. Oppikirjoissa markkinoiden sanotaan aina olevan tehokkaita, sijoittajien toimivan rationaalisesti ja maksimoivan hyötynsä. Tutkielma vastaa tutkimuskysymykseen hypoteesien avulla. Tutkielma on toteutettu käymällä läpi aiheeseen liittyvä teoreettinen tausta ja perehtymällä aiempaan kirjallisuuteen.
Keywords: käyttäytymistaloustiede; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|